Influence of Er, Cr: YSGG and Diode Lasers on The Surface Roughness of Enamel at Fissure area: An in vitro Study - Sara Abed Al Moneim Mohammed; Saher Sami Gasgoos (University of Mosul, College of Dentistry, 2023)
Aims: To assess and report the surface roughness incidence in fissure system of the dental enamel in human next Er, Cr: YSGG laser and Diode laser applications in order to examine anti-cariogenic impact and to compare the obtained results between the two laser types. Materials and Methods: Forty extracted impacted lower third molars teeth used in the experiment that should have an obvious occlusal fissure. Intact lower third molar were collected, which were free from caries .Teeth roots cut from crowns and crowns were divided bucco - lingually to two parts equally which were applied in 4 category included control group without any treatment, acid group only immersed in demineralizing solution, Diode laser group in which samples subjected to Diode laser (at wavelength 980nm, power 5 watt, mode P3, the time was 30 second) then immersed in demineralizing solution PH 4.4 for 96 hr., and Er, Cr: YSGG laser group in which samples subjected to Er, Cr: YSGG laser (wave length 2780nm, pulse energy20 Hz with pulse mode (H-mode), time 10 second) then immersed in demineralizing solution pH 4.4 for 96 hr. Results: both types of lasers resulted in a less surface roughness of enamel at fissure area as compared to the acid group, and Diode laser had better effect than Er, Cr: YSGG. The differences were statistically significant among the four groups at p≤ 0.01. Conclusions: Diode and Er, Cr: YSGG lasers improved the enamel surface roughness when compared to acid group.